Analysis of bond behavior of injected anchors in masonry elements by means of Finite Element Modeling. (1st June 2020) - Ceroni, Francesca; Darban, Hossein; Luciano, Raimondo
Abstract: Injected anchors made of steel bars embedded in masonry elements by means of cement-based grout represented in the past a wide solution for avoiding out-of-plane mechanisms. Corrosion phenomena in steel bars reduced the effectiveness of such type of intervention over time. Innovative materials, as the Fiber Reinforced Plastic ones, can represent a suitable alternative to increase durability and performance of injected anchors. Since the effectiveness of injected anchors is strictly related to bond behaviour along both the bar-grout and the grout-masonry interfaces, a detailed analysis by means of a Finite Element model was developed for different types of bars embedded in masonry elements. The numerical model was firstly calibrated on some experimental results of pull-out tests available in literature and, then, is used for investigating the effects of several parameters on both local and global behaviour. Load-displacement curves and local distributions of shear stresses are examined in detail. The numerical analyses evidenced that the maximum tensile force in the anchor mainly depends on the shear strength of the bar-grout and the grout-masonry interfaces and on the embedded length, but for very long embedded length, it can be limited by the tensile failure in the anchor or in the masonry.